The Influence of Nutrition Education Media (Brochures, Videos & Fans) on Increasing Knowledge and Attitudes of Balanced Nutrition on Worker Productivity at PT X & PT Z Karawang - Silaen, Cristhin Lusiana; Kurniasari, Ratih; Andriani, Eka (Universitas Ibn Khaldun Bogor, 2025)
In the national industrial sector, good and competent workers are needed, so it is necessary to increase worker productivity so that a company can compete with other companies. Productivity is a comparison between output and input relating to a person's ability to complete work based on the specified time. Factors that influence work productivity are the physical condition or nutritional status of a worker. Education can increase knowledge, attitudes and healthy living behavior. Providing nutrition education can be done using various media such as auditive, visual and audiovisual media. The aim of this research is to determine the effect of nutritional education media (brochures, videos & fans) on increasing knowledge and attitudes towards balanced nutrition on worker productivity. Quasi experimental research with a pretest and post-test group design. The sampling technique uses simple random sampling. The research sample consisted of 30 respondents. The results of the Paired Sample T-test show the influence of nutrition education media on increasing knowledge and attitudes about balanced nutrition on the productivity of PT. Based on the results of the paired sample t-test, it is known that there is a significant influence of providing nutrition education (brochures, videos and fans) on increasing knowledge and attitudes towards balanced nutrition on worker productivity.